Detección de la presencia del ácaro (Aculops lycopersici) causante del bronceamiento del tomate (Lycoprsicon esculentum) en El Salvador, América Central - Serrano Cervantes, Leopoldo (2016)
In October 1989, microscopic specimens of (acaros) with symptoms of browning and plant mortality in young and older tomato plants from various locations in El Salvador were sent tó the entomologist Ing. Ronald Ochoa from Costa Rica. lng. Ronald Ochoa is associated with the Diagnostics Network of the Centro Agronomico Tropical de Investigation y Enseñanza (CATlE) based in Turrialba, Costa Rica. Microscopic examination of this material confirmed the taxonomic identification as Aculops lycopersici (Acariformes: Eriophyidae), suspected since May 1988 with the first observation and collection of samples. Abrief review of literature and a phone conversation with the specialist who identified the material, permits reporting for the first time of the presence of this species in El Salvador. This finding is a warning about this pest which could be apotential problem in the tropics of Central America. This paper discusses personal observations of some of the characteristics, habits and appearances of this species, small experiments, and it includes a review of literature pertinent to this subject